2017
DOI: 10.2503/hortj.mi-156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for Flesh Mealiness in Apple (<i>Malus</i> × <i>domestica</i> Borkh.)

Abstract: During apple (Malus × domestica Borkh.) storage, a loss in fruit firmness can occur. This is frequently associated with mealiness, an undesirable trait. There have been studies, such as phenotypic analyses and transcriptomics, as well as others employing a transgenic approach, focusing on this trait. Certain genetic approaches, such as quantitative trait loci (QTL) approach, however, have not been attempted. In this study, to identify and characterize QTLs controlling flesh mealiness and to investigate their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…For mealiness, another QTL associated with MdPG1 was detected from different F 1 population [40]. So far, as 'Fuji' descendant, however, 90% of selected cultivars or superior breeding lines have inherited the haplotype of 'Fuji'-derived 'Ralls Janet' at the region of chr1 [10,48].…”
Section: Apple Cultivars and Texture Measurementmentioning
confidence: 99%
“…For mealiness, another QTL associated with MdPG1 was detected from different F 1 population [40]. So far, as 'Fuji' descendant, however, 90% of selected cultivars or superior breeding lines have inherited the haplotype of 'Fuji'-derived 'Ralls Janet' at the region of chr1 [10,48].…”
Section: Apple Cultivars and Texture Measurementmentioning
confidence: 99%
“…Therefore, there has been a concentrate on the rmness in apple breeding in order to maintain post-harvest fruit quality during long-term storage. According to other studies of QTL for esh rmness, genetic loci related to esh rmness were appeared on chromosome 10 including genomic regions for candidate genes such as 1-aminocyclopropane-1-carboxylate oxidase (ACO) and polygalacturonase (PG) located up to these QTL regions [2,[5][6][7]18]. In this study, meaningful GWAS peaks for esh rmness were found on chromosomes 17, 1, 3, 4, 5, 16, and 10, and SNPs (chromosome 10: 12900899, 28459403) most signi cantly associated with rmness were located 5Mb upstream of PG1 (MDP0000326734) and 4Mb downstream of ACO1 (MDP0000195885).…”
Section: Discussionmentioning
confidence: 99%
“…is an economically important temperate fruit-tree crop [1], and its industry is globally relatively large. For more advancement of apple industry, many apple breeders are keen interested in development of novel cultivars with high fruit quality traits such as richness of titratable acidity (TA), soluble solids content (SSC), skin color, esh rmness, and weight, which are major factors attracting to consumers' preferences [2][3][4][5][6][7]. However, production of new apple cultivars from conventional breeding is relatively slow and unpredictable owing to its self-incompatibility, high heterozygosity, complex traits controlled by multi loci, and relatively long juvenile period that makes it time-consuming to con rm the traits of the fruit compared with annual crops [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…major factors attracting to consumers' preferences [2][3][4][5][6][7]. However, production of new apple cultivars from conventional breeding is relatively slow and unpredictable owing to its self-incompatibility, high heterozygosity, complex traits controlled by multi loci, and relatively long juvenile period that makes it time-consuming to confirm the traits of the fruit compared with annual crops [3,8,9].…”
mentioning
confidence: 99%